Collaborative governance in the management of Tirta Agung Tourism Village Sukosari Kidul Village Bondowoso Regency - Andre Pratama Anhar; I Ketut Mastika; Panca Oktawirani (ARISTO, 2026)
This research aims to examine Collaborative Governance management of tourist villages. The research was conducted in the tourist village of Tirta Agung, Sukosari Kidul Village, Sumber Wringin District, Bondowoso Regency. The research method used is qualitative, data collection methods are carried out by interviews, observation and documentation. The results of the research show that the development of tourist destinations in Sukosari Kidul village was initiated by non-governmental organizations, namely the Sukosari Kidul village youth covil society. Collaborative governance in the management of the Tirta Agung Tourism Village destination, the stakeholders involved have different resources, this is a factor in collaboration. Collaborative management of the Tirta Agung Tourism Village can be said to fulfill the elements of the Collaborative Governance model according to Ansell and Gash which consists of institutional design and the village head of Sukosari Kidul as the facilitative leadership of the collaborative management of the Tirta Agung Tourism Village as well as in terms of a collaboration process which includes face-to-face dialogue,Â  joint commitment, shared understanding and intermediate outcomes/benefits. The collaboration that took place in Sukosari Kidul village can be said to be successful, but the joint commitment is still not optimal. The success achieved in the collaboration between civil society, namely the Pokdarwis and the Sukosari Kidul village government, namely the Tirta Agung Tourism Village, succeeded in becoming 2nd place in the award for the best Indonesian Tourism Village in the pioneer category (ADWI) 2022.